AKTUALISASI NILAI KEMANUSIAAN DALAM EKONOMI LOKAL: ANALISIS INTERDISIPLINER PRODUKSI GULA MERAH TEBU DI JORONG SURAU LUBUAK - Ilham, Fadli; Nuril Fahmi, Merdila; Meiweni Basra, Sri; Hafid, Fathurrahman; Surya, Wirma (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This article examines the actualization of the Pancasila principle of Just and Civilized Humanity in brown cane sugar production in Jorong Surau Lubuak, Nagari Tigo Balai, Matur District, Agam Regency, through an interdisciplinary perspective. The study employed descriptive qualitative field research. Primary data were collected directly by the research team from 19 December 2025 to 19 January 2026 through observation, structured interviews, and documentation involving producers, collectors or buyers, religious figures, and nagari officials. Official nagari documents were used as supporting data. The data were analyzed through data reduction, data display, conclusion drawing, and triangulation of sources and techniques. The findings show that human values are reflected in the selection of suitable sugarcane, cleanliness of equipment and production sites, limited and disclosed use of natural additives, truthful product-quality information, accurate weighing, quality-based price adjustments, agreed profit-sharing, waste reuse, and smoke control. However, unequal access to production machinery, informal agreements, limited product documentation, and weak institutional support constrain consistent protection. Interdisciplinary analysis identifies complementary development pathways: civic education for ethical governance, information technology for records and traceability, English for product communication, sports education for occupational health and ergonomics, and art for visual identity and culturally grounded packaging. The study concludes that human values in the local economy require ethical conduct, appropriate technology, and accessible institutional support.